2020
DOI: 10.1093/nutrit/nuaa036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose and sucrose on cognition in healthy humans: a systematic review and meta-analysis of interventional studies

Abstract: Context Evidence suggests that plasma glucose levels may influence cognitive performance, but this has not been systematically reviewed and quantified. Objective The aim of this review was to investigate the potential effects of glucose and sucrose, compared with placebo, on cognition in healthy humans. Data Sources The electronic databases PubMed and Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…76 In adults, consumption of glucose has shown a beneficial effect on immediate recall tasks in verbal memory assessments. 77 A meta-analysis of interventional and observational studies showed no effects on cognitive function of consumption of sweeteners in children or adults. 78 Compared with sugar consumption, however, multiple studies showed that consumption of the artificial sweetener aspartame is associated with poor cognitive performance.…”
Section: Sugars and Sweetenersmentioning
confidence: 99%
“…76 In adults, consumption of glucose has shown a beneficial effect on immediate recall tasks in verbal memory assessments. 77 A meta-analysis of interventional and observational studies showed no effects on cognitive function of consumption of sweeteners in children or adults. 78 Compared with sugar consumption, however, multiple studies showed that consumption of the artificial sweetener aspartame is associated with poor cognitive performance.…”
Section: Sugars and Sweetenersmentioning
confidence: 99%
“…The dynamic utilization of glucose by the cerebral cortex over the course of development suggests that the relative apportionment of glucose must also be dynamic ( 45 ), and since the glucose cannot be stored in the brain, at the right level of sugar intake, SSBs may raise the blood sugar level in the brain and boost brain metabolism, leading to higher cognitive scores ( 46 ). The result of a systematic review and meta-analysis of interventional studies also revealed modest beneficial effects of glucose on cognition, particularly recognition memory and attention processes ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we included studies that used ingestion of a glucose beverage as a control condition since an increasing number of studies include this method as a comparison to fasting. Evidence shows that ingesting even small amounts of glucose in a fasted state can impact physiology and cognition similarly to eating [32,33]. We had no inclusion or exclusion criteria specific to water ingestion, duration of a fast, nor the number of fasts the participant completed (i.e., fasting could have been short-or long-term or conducted multiple times akin to intermittent fasting so long as a fasted and non-fasted condition were compared).…”
Section: Methodsmentioning
confidence: 99%